Do penguins care about their neighborhood? Population implications of bioerosion in Magellanic penguin, Spheniscus magellanicus, at Martillo Island, Beagle Channel, Argentina - Scioscia, Gabriela (2024)
Intrinsic and extrinsic factors, such as bioerosion at nesting sites, regulate population dynamics and are relevant for the long-term conservation of penguins. Colony trends (between 2004-2022), were studied in a Magellanic penguin colony on Martillo Island, Beagle Channel, Argentina and compared between zones with contrasting degrees of erosion (high, medium, low). Individuals from each zone were characterized for foraging ecology, stress, and reproductive performance during the 2017-2018 breeding season to better understand the colony dynamics. foraging ecology, health, and reproductive output (for the 2017-2018 breeding season) were studied in a Magellanic penguin colony on Martillo Island, Beagle Channel, Argentina and compared between zones with contrasting degrees of erosion (high, medium, low). Changes in nest abundance varied in magnitude between nesting zones with different characteristics of occupation time, density and erosion. Declines in nest abundance in the densest, most eroded and longest occupied zone suggests that environmental degradation may be limiting the colony's carrying capacity.The colony size grew sharply until 2008, remained stable with fluctuations for several years, and slightly decreased over the recent ones. The decline was steeper within the high and medium erosion zones while the abundance remained relatively stable in the low erosion zone. A higher percentage of late breeders (probably younger breeders) occupied the less eroded and more recently occupied zone. Foraging, breeding and health parametersstress stress barely differed between zones. New individuals recruiting into the breeding colony choose select less eroded zones, either to reduce competition for nests or to avoid other effects of erosion and high-density areas. If this is the mechanism behind the shift in numbers throughout the island, we expect the island to be progressively occupied to the west. If competition or other density dependent factors are at play, a time will come when the vacant east side will begin to be recolonized by younger individuals. ButHowever, if erosion or other longer time -term effects spread throughout the islandare at play, recolonization may not occur and the colony may ultimately be abandoned as individuals search for new breeding grounds.